Assistance of MSMEs in the Practical Method of Preparing Financial Statements in the Joint Business Group (KUB) Berkah Pemalang - Suripto, Suripto; Prasetya, Victor (IMPOWERMENT SOCIETY, 2022)
The purpose of this community service activity is to help MSMEs of the Joint Business Group (KUB) Blessings of Karangasem Pemalang Village compile their financial reports simply, encourage orderly bookkeeping of transactions that occur daily, and motivate MSME participants to be able to record books so that expenses can be measured. Revenue and profits earned and knowing how your business is doing. For mentoring, using participatory techniques, participants participate in group discussions, share positive and negative experiences, and explore new lessons together. And after mentoring is carried out, participants are asked to implement what has been learned accompanied by the servicer. In conclusion, the activity went smoothly. All participants enthusiastically participated in the event until it was over and were optimistic that they would feel the benefits of mentoring for the progress of their business.